Association between temporomandibular disorders and anxiety: A systematic review - Santos, Erick Alves dos; Peinado, Beatriz Rodrigues Risuenho; Frazão, Deborah Ribeiro; Né, Yago Gecy de Sousa; Fagundes, Nathalia Carolina Fernandes; Magno, Marcela Baraúna; Maia, Lucianne Cople; Lima, Rafael Rodrigues; Souza-Rodrigues, Renata Duarte de (Frontiers in Psychiatry, 2022)
Temporomandibular Joint Dysfunction (TMD) is an umbrella term that includes musculoskeletal and neuromuscular conditions affecting the temporomandibular joint. The present systematic review aims to verify whether there is a specific association between TMD and anxiety. The searches were carried out in electronic databases, including PubMed, Scopus, Web of Science, and LILACS, the grey source OpenGrey, and Google Scholar, without restrictions on publication date and language. The acronym PECO was used, whose participants (P) were humans exposed to Temporomandibular joint dysfunction (TMD) (E), compared to participants without TMD (C) and the presence of anxiety as an outcome (O). After the search retrieval, the duplicates were removed, and the articles were evaluated by title and abstract, following our inclusion and exclusion criteria; then, the papers were read and thoroughly assessed. . After selection, the methodological quality was performed using the Newcastle-Ottawa Scale (NOS) for observational studies. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tool was used to assess the level of evidence. A total of 710 studies were found, and 33 articles were considered eligible and were included for the qualitative synthesis and the level of evidence assessment. The studies confirmed the association between anxiety and DTM, although there was a low certainty of evidence among the selected studies. Most articles showed a low risk of bias. Although the limitations of this systematic review, it is suggested a significant association between anxiety and TMD, as well as highlights possible directions for future research.